Laporan Kasus: Pemberian Misoprostol pada Kasus Abortus Inkomplit - Siti Shafira Elfreda; Sawitri, Lintang Lestari Cahya; Rahmadani, Nabila Yoli; Zulfadli, Zulfadli (Medula, 2024)
Abortion refers to the termination of pregnancy before 20 weeks of gestation or when the fetal weight is below 500 grams, typically due to fetal non-viability outside the uterus. Globally, there are over 2.3 million cases reported annually. Incomplete abortion is characterized by the presence of an open cervical ostium and bleeding, where all the products of conception are incompletely expelled from the uterus or do not correspond with the expected gestational age. This case study reports on incomplete abortion in a 26-year-old nulligravid woman presenting with vaginal bleeding. Clot discharge indicated expulsion of conception products, leading to a diagnosis of incomplete abortion at 12 weeks and 9 days of gestation (G1P0A0). Currently, misoprostol remains the preferred pharmacological intervention as Drug of Choice in cases of incomplete abortion. However, in practice, there are several ways to administer misoprostol, either sublingually, orally or vaginally. Several health organizations have their own protocols for administering misoprostol for cases of incomplete abortion. This case report will discuss misoprostol administration in patients with incomplete abortion.